Amniocentesis increases level of anxiety in women with invasive prenatal diagnosis of Down syndrome - Yanuarita Tursinawati; Serene Thain; Christina Choi; George Heong Yeo Seow (Faculty of Medicine, Universitas Trisakti, 2015)
Backgound Invasive prenatal diagnosis (PND) through amniocentesis and chorionic villus sampling (CVS) can detect Down syndrome. Pregnant women usually experience a variety of psychological responses associated with invasive PND. This study is intended to assess depression, anxiety and stress levels and the factors related to their psychological responses in pregnant women with invasive prenatal diagnosis of Down syndrome.Methods A cross sectional study was conducted at Kandang Kerbau Women’s and Children’s Hospital, Singapore. The psychological responses of 70 women undergoing PND were assessed by Depression Anxiety Stress Scale 21 (DASS 21) questionnaire. A multiple linear regression analysis was used to analyze association between knowledge and perceived risk with psychological responses (CI 95% and significance value p<0.05).Results More than half of the participants had normal anxiety (55.7%), stress (72.8%), depression levels (65.8%). The results revealed significantly higher level of anxiety in women with gestational age >13 weeks who had pursued amniocentesis. Women with no previous children had higher levels of depression and stress. Women who pursued amniocentesis had significantly higher anxiety scores compared to women undergoing CVS (p=0.015).Conclusions Women’s psychological responses are associated with gestational age, type of procedure and parity. The level of anxiety increased in women who underwent amniocentesis for diagnosis of Down syndrome. Knowledge and perceived risk of having a baby with Down syndrome do not seem to have psychological effects to women.